Chemical profile of volatile compounds and essential oil off Lippia alba (Mill) N.E. Brown (Research, Society and Development, 2022)
Lippia alba (Mill) N E Brown, populary know as lemongrass, is a native species of wide competition in Brazil, its leaves are used in folk medicine as a calming, analgesic and spasmolytic. The literature reports at least three chemotypes of the species: citral-myrcene, citral-limonene and carvona-limonene and their identification is important for correct pharmacological use. The objective of this article is to present the evaluation the chemical profile of the volatile components and essential oil, with subsequent identification of the chemotype of L. alba, found in the research campus of the Museu Paraense Emilio Goeldi, through gas chromatography to mass spectrometry (GC-MS). The results suggest that the analyzed chemotype is citral-myrcene, that “citral A” was not identified in the chemical profile of the flowers and that the hydrodistillation technique of the leaves revealed a higher yield in the contents of the major components of the leaf in relation to the simultaneous distillation and extraction technique.